2020
DOI: 10.1038/s42255-020-00312-4
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen recycling buffers against ammonia toxicity from skeletal muscle breakdown in hibernating arctic ground squirrels

Abstract: Hibernation is a state of extraordinary metabolic plasticity. The pathways of amino acid metabolism as they relate to nitrogen homeostasis in hibernating mammals in vivo is unknown. Here we show, using pulse isotopic tracing, evidence of increased myofibrillar (skeletal muscle) protein breakdown and suppressed whole body production (WBP) of metabolites in vivo throughout deep torpor. As WBP of metabolites is suppressed, amino acids with nitrogenous side chains accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 70 publications
1
23
0
Order By: Relevance
“…The purpose of the energetically expensive arousals from torpor is not known, although, at least in lemurs, they appear to be compelled only in animals exhibiting torpid Tb < 30 • C (Dausmann et al, 2004). Clearly rates of biochemical reactions slow as Tb decreases during torpor, and differences in the thermal sensitivity of various reactions throughout the body leads to widespread changes, both increases and decreases, in the relative abundances of metabolites, transcripts and proteins across the torpor bout; the short, warm arousal periods are also highly dynamic, with changes between initial rewarming through the beginning of cooling when the next bout of torpor begins (Nelson et al, 2009;Epperson et al, 2011;Hindle et al, 2011Hindle et al, , 2014Jani et al, 2012;Grabek et al, 2015a;Bogren et al, 2017;D'Alessandro et al, 2017;Regan et al, 2019;Rice et al, 2020). While rewarming restores the slowed cellular processes and biochemical reaction rates of torpor in every system in the body, the detailed molecular mechanisms orchestrating these dynamics remain to be fully elucidated (see van Breukelen and Martin, 2015, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the energetically expensive arousals from torpor is not known, although, at least in lemurs, they appear to be compelled only in animals exhibiting torpid Tb < 30 • C (Dausmann et al, 2004). Clearly rates of biochemical reactions slow as Tb decreases during torpor, and differences in the thermal sensitivity of various reactions throughout the body leads to widespread changes, both increases and decreases, in the relative abundances of metabolites, transcripts and proteins across the torpor bout; the short, warm arousal periods are also highly dynamic, with changes between initial rewarming through the beginning of cooling when the next bout of torpor begins (Nelson et al, 2009;Epperson et al, 2011;Hindle et al, 2011Hindle et al, , 2014Jani et al, 2012;Grabek et al, 2015a;Bogren et al, 2017;D'Alessandro et al, 2017;Regan et al, 2019;Rice et al, 2020). While rewarming restores the slowed cellular processes and biochemical reaction rates of torpor in every system in the body, the detailed molecular mechanisms orchestrating these dynamics remain to be fully elucidated (see van Breukelen and Martin, 2015, and references therein).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, urea reabsorption, together with water and other substances, from the bladder epithelium to the bloodstream has been shown (Nelson et al, 1973 , 1975 ). Many studies suggest that urea recycling also occurs in hibernating rodents (Galster and Morrison, 1975 ), urea cycle intermediates remaining at stable levels during torpor, which is consistent with the suppression of the urea cycle (Rice et al, 2020 ). Accordingly, genes involved in the urea cycle have been shown to be downregulated in the liver of torpid golden-mantled ground squirrel (Williams et al, 2005 ).…”
Section: Maintenance Of Lean Body Mass In Hibernators During Wintermentioning
confidence: 61%
“…Moreover, a selective enrichment of several essential amino acids in the plasma from hibernating ground squirrels has led the authors to hypothesize a mechanism whereby they are spared and recycled for use in new protein synthesis during the winter fast (Epperson et al, 2011 ). Nitrogen recycling has been investigated recently in hibernating arctic ground squirrels (Rice et al, 2020 ). It was notably shown that slow rates of skeletal muscle protein breakdown during torpor may provide a source of (essential) amino acids and that the free nitrogen released during protein breakdown is recycled and buffered by transamination, with accumulation in glutamine, glutamate, and alanine.…”
Section: Maintenance Of Lean Body Mass In Hibernators During Wintermentioning
confidence: 99%
See 1 more Smart Citation
“…Obligate hibernators, like the arctic ground squirrel, have endogenously timed annual dormancy in winter where they generate energy reserves during the warmer months and then that energy is conserved through a large reduction of basal metabolic rate, heart rate, blood flow, and temperature while they hibernate (Loren and Barnes, 1999;Singhal et al, 2020). Arctic ground squirrels can hibernate for up to 8 months out of every year and during this hibernation they lower their body temperature to adopt the lowest body temperature ever measured in a mammal (-2.9 • C) (Loren and Barnes, 1999;Buck et al, 2008;Richter et al, 2015;Singhal et al, 2020;Rice et al, 2020). Arctic ground squirrels recycle broken down nutrients while in hibernation to enable survival (Rice et al, 2020).…”
Section: Obligate Hibernationmentioning
confidence: 99%